The essay of a ‘neue Aufklärung’ as a prelude to the future ‘experimental philosophy’ in Nietzsche - Barelli, Maria Cecilia (Anales del Seminario de Historia de la Filosofía, 2020)
We propose to explore the reception of the Enlightenment in Friedrich Nietzsche. We find in his published and posthumous writings not only an evaluation or critical balance of the scope of this movement in its different expressions, but also the attempt to continue with some of his tasks, based on an experimental philosophical praxis. We consider, therefore, that the Aufklärung’s notion, with the twists and turns sketched by the German thinker himself, deserves a renewed and careful analysis, both for the contributions that can be made in the field of critical and historical exegesis of the corpus Nietzschean, as well as the possibility of reconstructing in part the way in which the Enlightenment influx entered into the European philosophy of the mid and second half of the nineteenth century.